Deep phenotype characterization of hypertensive response to exercise: implications on functional capacity and prognosis across the heart failure spectrum. (29th March 2023) - Pugliese, Nicola Riccardo; De Biase, Nicolò; Del Punta, Lavinia; Balletti, Alessio; Armenia, Silvia; Buralli, Simona; Mengozzi, Alessandro; Taddei, Stefano; Metra, Marco; Pagnesi, Matteo; Borlaug, Barry A.; Williams, Bryan; et al.
Abstract: Aims: Limited evidence is available regarding the role of hypertensive response to exercise (HRE) in heart failure (HF). We evaluated the systolic blood pressure (SBP) to workload slope during exercise across the HF spectrum, investigating haemodynamic and prognostic correlates of HRE. Methods and results: We prospectively enrolled 369 patients with HF Stage C (143 had preserved [HFpEF], and 226 reduced [HFrEF] ejection fraction), 201 subjects at risk of developing HF (HF Stages A–B), and 58 healthy controls. We performed a combined cardiopulmonary exercise stress echocardiography testing. We defined HRE as the highest sex‐specific SBP/workload slope tertile in each HF stage. Median SBP/workload slope was 0.53 mmHg/W (interquartile range 0.36–0.72); the slope was 39% steeper in women than men ( p < 0.0001). After adjusting for age and sex, SBP/workload slope in HFrEF (0.47, 0.30–0.63) was similar to controls (0.43, 0.35–0.57) but significantly lower than Stages A–B (0.61, 0.47–0.75) and HFpEF (0.63, 0.42–0.86). Patients with HRE showed significantly lower peak oxygen consumption and peripheral oxygen extraction. After a median follow‐up of 16 months, HRE was independently associated with adverse outcomes (all‐cause mortality and hospitalization for cardiovascular reasons: hazard ratio 2.05, 95% confidence interval 1.81–5.18), while rest and peak SBP were not. Kaplan–Meier analysis confirmed a worse survival probability in Stages A–B ( p = 0.005) and HFpEF ( p < 0.001), but not HFrEF. Conclusion: A steeper SBP/workload slope is associated with impaired functional capacity across the HF spectrum and could be a more sensitive predictor of adverse events than absolute SBP values, mainly in patients in Stages A–B and HFpEF. Abstract : Impact of hypertensive response to exercise on functional capacity and prognosis. Cumulative survival and relative risk of all‐cause mortality (ACM) and cardiovascular hospitalizations (CVH) after a median follow‐up of 16 months per tertile of systolic blood pressure (SBP)/workload slope. Unadjusted analysis (Kaplan–Meier survival curves) for the primary outcome in the whole patient population. Adjusted analysis (Cox proportional hazard ratios) illustrating higher mortality in the highest tertile of the SBP/workload slope. Hazard ratios are adjusted for age, sex, body mass index, arterial hypertension, diabetes mellitus, previous myocardial infarction, N‐terminal pro‐B‐type natriuretic peptide, rest and peak SBP, rest and peak cardiac output, rest and peak left ventricular ejection fraction, and medications (beta‐blockers and calcium channel blockers). AVO2 diff, arterial–venous oxygen content difference; CI, confidence interval; HFpEF, heart failure with preserved ejection fraction; sPAP, systolic pulmonary artery pressure; TAPSE, tricuspid annular plane systolic excursion; VAC, ventricular–arterial coupling; VO2, oxygen consumption.